SARS-CoV-2 convalescent plasma for the controlled clinical trial “COVIC-19”: experience from collection of very high-titer plasma from superimmunized individuals - Hoffmann, Simone; Seidel, Alina; Ludwig, Carolin; Vieweg, Christiane; Müller, Rebecca; Hofmann, Henrike; Jahrsdörfer, Bernd; Wuchter, Patrick; Klüter, Harald; Schmidt, Michael; Johnsen, Matthias; Burkhardt, Thomas; et al. (Transfusion, 2025)
Background COVID-19 convalescent plasma (CCP) is a treatment option for COVID-19. Understanding of donor and product characteristics is important for optimization of CCP therapy. We report the experience of collection of very high-titer CCP for the trial “A randomized open-label trial of early, very high-titer convalescent plasma therapy in clinically vulnerable individuals with mild COVID-19” (COVIC-19) (NCT05271929). Study Design and Methods Individuals who had recovered from COVID-19 and had ≥1 dose of a SARS-CoV-2 vaccine were recruited as donors for CCP. Anti-SARS-CoV-2 antibodies were measured by ELISA, and neutralization capacity against SARS-CoV-2 variants was assessed in surrogate and pseudovirus-neutralization assays. Correlation of antibody titers with donor characteristics and antibody kinetics was analyzed. Results We recruited 688 potential donors. 41.4% of individuals had antibody concentrations of ≥4000 BAU/ml (anti-SARS-CoV-2 IgG ELISA [QuantiVac]). Concentrations did not significantly differ by sex or ABO type, but were higher among those who had received at least three vaccinations. Highest titers were observed in those with a breakthrough infection after two vaccinations, followed by a booster (median 5374 BAU/mL) or breakthrough infection after the 3rd or 4th vaccination (median 3846 BAU/mL). Ultimately, 172 eligible individuals donated CCP with a median concentration of 6858 BAU/mL (range 4015-22,923 BAU/mL). Discussion We demonstrate the feasibility of the collection of very high-titer CCP products under a harmonized protocol for a randomized clinical trial, but it requires substantial donor selection, appropriate antibody assays, rapid succession of screening, and apheresis to take advantage of the short period of very high antibody concentrations.